2021
DOI: 10.1177/14759217211033625
|View full text |Cite
|
Sign up to set email alerts
|

Inspection interval optimization of aircraft landing gear component based on risk assessment using equivalent initial flaw size distribution method

Abstract: The nondestructive inspection interval is highly related with both system reliability and maintenance burden. Conventional inspection interval decision criteria based on the deterministic crack propagation analysis could require too much frequent inspection or sometimes occur structural failure owing to the rapid crack propagation than expected. The stochastic crack growth analysis method was proposed to compensate for the shortcomings of the deterministic analysis. This research studied the crack growth of ai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 12 publications
(18 reference statements)
0
15
0
Order By: Relevance
“…It was reported that performing NDT resulted in a highly conservative design 4 . The reason for this is discussed herein based on discretized crack length distributions for simplicity 11 . The crack length distribution after an inspection at cycle N can be expressed as truepxtruêk=pNxtruêk1Lxtruêk+p0xtruêkLxtruêk, where p N is the probability mass function (PMF) for the crack length distribution at cycle N , p 0 the PMF for the initial crack length, and L the POD.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…It was reported that performing NDT resulted in a highly conservative design 4 . The reason for this is discussed herein based on discretized crack length distributions for simplicity 11 . The crack length distribution after an inspection at cycle N can be expressed as truepxtruêk=pNxtruêk1Lxtruêk+p0xtruêkLxtruêk, where p N is the probability mass function (PMF) for the crack length distribution at cycle N , p 0 the PMF for the initial crack length, and L the POD.…”
Section: Resultsmentioning
confidence: 99%
“…This method is known as the equivalent initial flaw size (EIFS) method. Information regarding the crack shape, loading history, and crack growth law is required when using the EIFS method 11 …”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations